Transoral robotic surgery for laryngeal cancer. Issue 2 (April 2015) - Mendelsohn, Abie H.; Remacle, Marc
Abstract : Purpose of review: Transoral robotic surgery (TORS) has seen substantial surge since its introduction in around 2007. Although initially described for cancer of the oropharynx, advances in robotic instrumentation and endoscopy have allowed for application of TORS toward laryngeal cancer. This review discusses the recent published experience of TORS for laryngeal cancer. Recent findings: TORS supraglottic laryngectomy continues to be the most frequent application of robotic surgery for laryngeal cancer. A number of case series have described the positive experience with TORS supraglottic laryngectomy with both oncologic and functional outcomes rivaling alternative therapy options. TORS total laryngectomy also continues to be applied in selective cases for laryngeal cancer. The objectives of TORS total laryngectomy is to reduce the size of the resultant pharyngotomy and to limit the lateral exposure of the cervical vessels. Although limited in numbers, TORS total laryngectomy appears to be a technique of increasing application. TORS approach for primary glottic cancer has also been described in limited case series. Although the majority of patients demonstrated positive outcomes following TORS glottic cordectomy, this technique may still require additional advancement of robotic technology before widespread application is seen. Summary: A TORS approach for laryngeal cancer is increasing in application and utility. The major surgical procedures described to date include supraglottic laryngectomy, total laryngectomy, and glottic cordectomy with promising results.